Novel and legacy per- and polyfluoroalkyl substances in humans: Long-term temporal variability and metabolic perturbations - Che-Jung Chang; Anna S. Young; Alexander Keil; Catherine E. Mullins; Donghai Liang; Shanshan Zhao; Dean P. Jones; Xin Hu; Douglas I. Walker; Alexandra J. White (Environment International)
As legacy per- and polyfluoroalkyl substances (PFAS) are phased out, numerous substitutes have emerged, raising concerns about their potential health impacts. Using targeted and untargeted approaches, we evaluated plasma PFAS on an –omic scale, examining temporal variability and associated metabolomic disruptions. A total of 400 blood samples from 200 Sister Study participants (collected in 2007–2008 and 2013–2014) were analyzed using liquid chromatography with high-resolution mass spectrometry. Temporal variability was assessed using Spearman correlations and intraclass correlation coefficients. Network analysis, metabolome-wide association studies, and pathway analysis were used to evaluate the impacts of PFAS mixtures on the human metabolome. We detected 24 legacy PFAS via the targeted approach and 1,802 features annotated as potential PFAS via the untargeted approach (21 confirmed by reference standards). While legacy PFAS demonstrated low temporal variability, novel PFAS, especially those that have increased in abundance over time, demonstrated greater temporal variability. The legacy PFAS mixture was associated with lipid and amino acid metabolism, while other PFAS mixtures consisting of novel PFAS affected a wider range of metabolic pathways in addition to amino and lipid metabolism, such as carbohydrate, cofactor and vitamin, and endocrine metabolism. These findings underscore the need for further research on these novel PFAS and their health effects.